STUDENTS’ PERCEPTION ON THE USE OF WHATSAPP FOR LEARNING ENGLISH AT SMP ISLAM AS-SHOFA - Sri Wahyuni; Jismulatif Jismulatif; Mahdum Mahdum (JURNAL PAJAR (Pendidikan dan Pengajaran), 2022)
This study aims to determine students' perceptions of the use of WhatsApp for learning English in SMP Islam As-Shofa and the differences between male and female perceptions about use Whatsapp. This research is a quantitative descriptive study involving 2 classes totaling 50 students. The instrument used is a questionnaire to get data easily during the pandemic. Data collection was carried out by distributing online questionnaires to 9th-grade students of SMP Islam As-Shofa via group Whatsapp to the students. The data were analyzed using a Likert scale to determine students' perceptions of using Whatsapp for learning English. The results showed that learning through whatsapp was quite feasible to use with the results of a percentage of 40% having a positive perception and for the difference between male and female students with a percentage of 24.4% of male students answering agree for positive perception, and with a percentage of 21% female students answering agree for positive perception, while for the negative perception, the result with a percentage 45.2% students answered disagree and with a percentage 22.4% female students answered disagree.